Geophysics of the Canary Islands Results of Spain$1 (Bs Exclusive Economic Zone Program /s - Clift, Peter; Acosta, Juan.; SpringerLink (Online service) (Dordrecht : Springer Netherlands, 2005)
This book contains the results of a 9 year (1995-2004) investigation of the Canary Islands Exclusive Economic Zone, using state of the art technology. The main result areas are: a multibeam survey demonstrating the magnitude of catastrophic failures of the Canary Islands; a comparison of the morphology of the Canary Islands with Hawaii; the significance of hydrothermal activity in the Canary Channel associated with Mesozoic salt diapirs; an analysis of the morphology and structure of the offshore extension of the Anaga massif in Tenerife island; a detailed description of the archipelago gravity field and magnetic field of the Canary Islands. All in all the wealth of new data and ideas presented in this collection of papers has rarely been equaled in an investigation of an oceanic island group. This book is very useful for researchers, graduates and undergraduates interested in ocean research. Reprinted from Marine Geophysical Researches Vol. 24 : No. 1-2, 2003.
Geologic evolution of the Canarian Islands of Lanzarote, Fuerteventura, Gran Canaria and La Gomera and comparison of landslides at these islands with those at Tenerife, La Palma and El Hierro -- Salt Diapirs, Salt Brine Seeps, Pockmarks and Surficial Sediment Creep and Slides in the Canary Channel off NW Africa -- Comparison of volcanic rifts on La Palma and El Hierro, Canary Islands and the Island of Hawaii -- Morphological and structural analysis in the Anaga offshore massif, Canary Islands: fractures and debris avalanches relationships -- Gravity analysis offshore the Canary Islands from a systematic survey -- A magnetic anomaly study offshore the Canary Archipelago -- Paleoearthquake evidence in Tenerife (Canary Islands) and possible seismotectonic sources -- Age and composition of the Amanay Seamount, Canary Islands.
Keywords: Earth sciences; Geology; Geophysics; Oceanography; Geographical information systems; Earth Sciences; Earth Sciences, general; Geophysics and Environmental Physics; Geophysics/Geodesy.; Geographical Information Systems/Cartography.; Geology; Oceanography; Electronic books